PD-1 derived CA-170 is an oral immune checkpoint inhibitor that exhibits preclinical anti-tumor efficacy - Pottayil G. Sasikumar; Naremaddepalli S. Sudarshan; Srinivas Adurthi; Raghuveer K. Ramachandra; Dodderi S. Samiulla; Anirudha Lakshminarasimhan; Anuradha Ramanathan; Talapaneni Chandrasekhar; Amit A. Dhudashiya; Sumalatha R. Talapati; Nagesh Gowda; Sreenivasulareddy Palakolanu; et al. (Communications Biology, 2021)
Sasikumar et al. describe the identification and characterization of CA-170, a small molecule inhibitor of PD-L1 and VISTA. They find that CA-170 activates T cells and exhibits anti-tumor efficacy in mouse models. This study highlights the potential of CA-170, which has advanced to human clinical trials, as an anti-cancer drug.